Analysis Of Public Information Services At The General Elections Commission (Kpu) Of Bengkulu Province - Imanda, Antonio; Saputra, Harius Eko; Lorita, Evi; Anjani, Nengsi Putri (Utan Kayu Publishing, 2022)
This study aims to analyze public information services provided by the General Elections Commission (KPU) of Bengkulu Province in an effort to increase community participation in the 2024 elections. A descriptive qualitative approach was used, with data collected through observation, in-depth interviews, and documentation. Agustinus’ strategy theory (1996), which includes strategy formulation, implementation, and control, served as the analytical framework. The results indicate that KPU Bengkulu implements public information services through a main strategy based on KPU Regulation No. 9 of 2022. Information is disseminated through various channels, including social media (Instagram, Facebook, YouTube), the E-PPID portal, and direct outreach programs such as goes to campus and goes to pesantren. These strategies are considered effective in conveying electoral information and encouraging public participation, particularly among first-time voters. However, challenges remain in building public trust in the importance of political engagement.